Daytime Surface Energy Fluxes over Soil Material Remediated Using Thermal Desorption. Issue 1 (29th November 2018) - O'Brien, Peter L.; DeSutter, Thomas M.; Casey, Francis X. M.; Daigh, Aaron L.M.; Heitman, Joshua L.; Derby, Nathan E.; Khan, Eakalak
Abstract : Core Ideas: Surface energy balance was quantified with micro‐Bowen ratio instrumentation. Surface energy balance was similar over native topsoil and soils treated with thermal desorption. Thermal desorption did not alter soil temperature dynamics or evaporation. A mix of topsoil and thermal desorption–treated soil matched surface energy balance of topsoil best. Remediation efforts to reduce contaminant concentrations in soils often alter soil properties. Since these alterations can affect the capacity of soil to function, their extent and magnitude may dictate future land use. This study addresses the suitability of soils for agricultural production after remediation of petroleum hydrocarbons using ex situ thermal desorption by quantifying the daytime surface energy balance prior to the growing season. The energy balance was quantified using micro‐Bowen ratio instrumentation to compare non‐contaminated topsoil (A) to both subsoil materials treated by thermal desorption (TD) and a 1:1 mixture (v/v) of TD and A (TDA). Despite differences in soil characteristics, the net radiation, soil heat flux, latent heat flux, and sensible heat flux were each similar among the three reclamation conditions over a period of 18 d. The fluctuations in these fluxes between the three conditions were attributed to natural variability, and they were not large enough to induce apparent inconsistencies in soil temperature dynamics or evaporative losses. Overall, these findings suggest the surface energy balance in thermal desorption–treated soils is similar to that of the native topsoil and that using a mixture of treated soils with native topsoil may even be a better representation of pre‐disturbance conditions.